(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Radiology holds an important role in evaluating patients with suspected stroke. It is therefore important to distinguish hyperacute or acute. DWI-ADC is an important modality. For ADC value measurement, it is more accurate to use multiple b value. There is a significant variability of ADC values in MRI depending on the coil system, imager, vendor, magnetic field strength and multicentre. The purpose of the study is to find out the difference of ADC value in hyperacute and acute stroke. Analytical observational study with cross sectional study approach to determine ADC values differences in Saiful Anwar Hospital Malang. Head MRI of 3T with 3 b values (0, 500, 1000) was performed on every subject. The data were analysed using descriptive statistic. Results: There were 12 subjects observed, 6 in the hyperacute group (onset <24 hours) and acute (onset 24 hours - 1 week). There was a significant difference with p<0.05 on average ADC (10-3 mm2 /s) and rADC (%) values between the hyperacute and acute groups. The ADC average mean ±SD of hyperacute (0.23 ± 0.05) was lower than acute (0.37 ± 0.04), and so as the ±SD rADC mean value of hyperacute (32 ± 8.1) was less than acute (52 ± 4.3). Conclusion: The ADC and rADC average values in the hyperacute were lower than that in the acute group.